An investigation of the cognitive processes in solving operational research problems among selected business degree undergraduates in Malaysia - Cheng, Sheila (2014)
Many studies and reports indicated that Malaysian graduates did not possess the required problem solving skills to meet the societal and industrial demand with the increase in complexity of problems nowadays. The crux of Operational Research is to equip students with problem solving skills. It also helps people to make better and informed decisions. Solving OR problems hinges on principles of cognitive psychology, but there is a dearth of research on cognitive processes in the domain of OR. This study explored the cognitive processes and pathways used by Malaysian undergraduate business degree students (UBD) in solving well-structured (WS) and ill-structured (IS) OR problems. The similaritioures and differences in these problem solving processes between the successful and unsuccessful problem solvers were identified. Forty-two UBD students from six tertiary institutions were selected for the case study. In-depth observations and interviews were conducted. The problem solving sessions using the ‘think aloud’ approach were audio- and video-recorded. For both OR problems, the cognitive processes were determined from behaviour and performance exhibited by participants while they were delineating the concepts, proposition and strategies in their solution paths. All written responses and transcripts of video-recordings and interviews in the problem solving sessions were transcribed, analysed and classified into episodes of strategies for the interpretations of the cognitive processes. The findings from this study reveal that the performance on the wellstructured problem was different from, and independent of, the ill-structured problems. For the well-structured problem, the cognitive processes of participants did not exhibit a straightforward linear pattern, while no non-linear pattern of cognitive processes was found in the cases of the ill-structured problem. This study also found similarities and differences in cognitive processes between successful and unsuccessful solvers. For the well-structured problem, successful solvers could recall, retrieve and relate the relevant concepts to the problem. For the unsuccessful solvers, they could not fully comprehend the problem although they indicated that they had learnt the relevant concepts and knowledge. For the ill-structured problem, both successful and unsuccessful solvers could recall, retrieve and relate concepts, knowledge and experiences relevant to the problem. The difference between the successful and unsuccessful solvers was the varying degrees in understanding and analysing the problem. Successful solvers spent more time in solving both the well- and ill-structured problems than the unsuccessful solvers. It was also found that pathways to solving well- and ill-structured problems influenced the individual’s decision-making outcomes. When the problem did not conform to certain patterns, participants had a freer hand to use their own preferred method(s) to solve (whether successful or otherwise) the problem and made the decision accordingly. Emanating from these findings, a (6+1)-Rs problem solving heuristic model has been proposed to ameliorate the cognitive processes of students in solving OR problems and the quality of decision making. The findings suggest significant implications for the development of effective OR pedagogy and improvement in the design of instructional materials.